Perancangan Sistem Informasi Pembayaran Administrasi SMK Negeri 1 Jiwan - Pamungkas, Ridho (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2017)
The rapid development of technology requires schools to provide optimal service to their students, especially in SMK Negeri 1 Jiwan. Improve the quality of information systems is one way to support services to students. The administration payment information system is designed in accordance with the circumstances in the school. The data were collected using interview method and observation method. This research produce information system design using Microsoft Visual Basic 6.0 which can help SMK Negeri 1 Jiwan to give service in administration payment of student.